Development of a rapid recombinase polymerase amplification-lateral flow dipstick assay for sensitive detection of duck adenovirus type-3 - Sun, Jiayu; Liu, Kewei; Liu, Chao; Wang, Zhenyu; Gao, Jiaxi; Zhao, Ruya; Yuan, Long; Shen, Yan; Li, Jinchun; Chen, Fangfang (Frontiers in Microbiology, 2025)
Duck adenovirus type-3 (DAdV-3) infections have severe effects on duck health, and rapid detection methods are crucial to reduce the morbidity and mortality associated with this pathogen in clinical practice. In this study, we established, optimized, and validated a novel recombinase polymerase amplification (RPA)-lateral flow dipstick (LFD) assay for the detection of DAdV-3. Next, we established a clinical infection model based on the pathogenicity of the DAdV-3 strain and tested the effectiveness of the RPA-LFD assay in controlling an outbreak of DAdV-3 infection. The findings indicated that the RPA-LFD assay could be performed within 30 min at 42°C. Specificity tests indicated no cross-reactivity with other viruses. The detection limit of the assay was 1 × 101 copies/μL. We evaluated 65 clinical samples using RPA-LFD and quantitative polymerase chain reaction (qPCR), and both methods showed a positivity rate of 33.8% and a coincidence rate of 100%. The kappa (κ) value of the RPA-LFD and qPCR assays was 1 (p < 0.001). The application of this assay in experimentally infected ducklings reduced the mortality rate from 20 to 8%. Thus, the RPA-LFD assay established in this study demonstrated high specificity, sensitivity, rapidity, and efficacy, indicating its potential for rapid detection of DAdV-3 in clinical settings.